Associations between body shape, body adiposity and other indices: a case study of hypertension in Chinese children and adolescents - Yinghe Tong; Euna Han (Taylor & Francis Group, 2019)
Background: A Body Shape Index (ABSI) and the Body Adiposity Index (BAI) are used to quantify body shape for adults. However, only a few studies have been conducted confirming whether ABSI or BAI is a better index for predicating hypertension and pre-hypertension in Chinese children and adolescents. Aim: To estimate scaling exponents for using ABSI with Chinese children and adolescents, comparing body shape indices used for predicting hypertension and pre-hypertension and determine which obesity indices can serve as predictors. Subjects and methods: Data from children and adolescents aged 7-17 years in the 2011 Chinese Health and Nutrition Survey were analysed. Partial correlation analysis and receiver operating characteristics analysis were applied. Results: The area under curve (AUC) values for all the predictors are better for differentiating hypertension than pre-hypertension. Body Mass Index (BMI) gave the largest AUC in both children and adolescents. ABSI and ABSI-(C) (ABSI for Chinese children and adolescents) were unable to differentiate hypertension or pre-hypertension in the population. BAI could only differentiate pre-hypertension in girls aged 7-12 years (AUC = 0.353, p < 0.05). Conclusion: ABSI, ABSI-(C) and BAI are not more associated with hypertension or pre-hypertension than BMI, waist circumference and waist-to-height ratio in Chinese children and adolescents.